2011
DOI: 10.1644/10-mamm-a-009.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mammalian carnivore use of riparian ecosystems in Mediterranean climates

Abstract: Riparian ecosystems serve as movement and dispersal corridors; however, the factors that determine their use by multiple species of carnivores remain unknown. Two hypotheses can explain carnivore presence in riparian ecosystems. Higher riparian plant richness, diversity, and structure provide the resources used by carnivores (resting sites, cover, and food). Alternatively, areas with higher water availability allow species to withstand water loss and thermal gradients in the high summer temperatures. In southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 67 publications
1
17
1
1
Order By: Relevance
“…For example, Hilty and Merenlender (2004) found that, although native mammalian predators (e.g., coyote, Canis latrans; raccoon, Procyon lotor) preferred wider riparian corridors, they nonetheless used narrower, human-disturbed corridors in agricultural landscapes. In addition, wildlife movement through road underpasses associated with rivers and streams is well documented (Clevenger and Waltho, 2000;Santos et al, 2011). Although disturbed riparian corridors are not the equivalent of undisturbed ones (Battin, 2004), this body of literature suggests that species will use disturbed riparian corridors when undisturbed ones do not exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hilty and Merenlender (2004) found that, although native mammalian predators (e.g., coyote, Canis latrans; raccoon, Procyon lotor) preferred wider riparian corridors, they nonetheless used narrower, human-disturbed corridors in agricultural landscapes. In addition, wildlife movement through road underpasses associated with rivers and streams is well documented (Clevenger and Waltho, 2000;Santos et al, 2011). Although disturbed riparian corridors are not the equivalent of undisturbed ones (Battin, 2004), this body of literature suggests that species will use disturbed riparian corridors when undisturbed ones do not exist.…”
Section: Introductionmentioning
confidence: 99%
“…The use of riparian areas for movement is species-specific (Gilbert-Norton et al, 2010;Lees and Peres, 2008). Nonetheless, multiple terrestrial species rely on riparian areas at some point in their life history (Naiman and Decamps, 1997), most commonly for migration through human-modified landscapes (Santos et al, 2011). Additionally, a variety of species use riparian corridors for access to water, escape from predators, cover, food, nesting habitat, and dispersal or movement between habitat patches (Brost and Beier, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Riparian zones in med-regions and other semiarid environments also host a large proportion of the surrounding biome's wildlife species for some portion of their life history (Patten, 1998;Seavy et al, 2009a). Examples of high diversity include mammalian carnivores (Matos et al, 2009;Santos et al, 2010), birds (Leal et al, 2011), and beetles (da Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Es posible que se trate de zonas de paso donde no haya poblaciones estables, zonas en las que el esfuerzo de muestreo no haya sido suficiente, en las que los individuos se encuentren en baja densidad o en las que el hábitat no sea el más apropiado. Puesto que los meloncillos en el sur de la Península tienen cierta preferencia por los sistemas acuáticos y ambientes riparios (Santos et al 2011), es probable que estos ambiente hayan jugado un papel crucial en la colonización de la provincia de Granada, en primer lugar a través de la cuenca del río Genil, e incluso de la del río Guadalhorce, y en segundo lugar a través de las grandes cuencas de los ríos Guadiana Menor y Guadalfeo (al norte y al sur de Sierra Nevada, respectivamente). De ser así, estas cuencas cumplirían de forma eficaz la función de corredores naturales, a través de los cuales los individuos dispersantes podrían estar colonizando ambas vertientes del macizo de Sierra Nevada.…”
Section: Discussionunclassified